The Role of Urate in Cardiovascular Risk in Adolescents and Young Adults With Hypertension, Assessed by Pulse Wave Velocity - Močnik, Mirjam; Golob Jančič, Sonja; Filipič, Martina; Marčun Varda, Nataša (Frontiers in Cardiovascular Medicine, 2022)
Background: Urate is increasingly recognised as a cardiovascular risk factor. It has been associated with hypertension, metabolic syndrome, obesity, chronic kidney disease and diabetes. Its prognostic role is less clear. The aim of our study was to evaluate the association between serum urate and pulse wave velocity, a measure of arterial stiffness in hypertensive adolescents and young adults. Methods: 269 adolescents and young adults with hypertension were included in the study. In all, anthropometric, blood pressure, pulse wave velocity and serum urate measurements were made. Variables were compared between gender, participants with or without obesity and with or without elevated urate. Results: In multiple regression analysis for urate as dependent variable gender and diastolic pressure were found to be statistically significant. The difference between urate levels were found between boys and girls (p<0.001), obese and non-obese (p<0.001); however, pulse wave velocity did not differ between hyper- and eu-uricemic group (p=0.162). Conclusions: Associations between urate, gender, diastolic blood pressure and obesity were confirmed, however, no significant associations between pulse wave velocity and urate were detected.